M & A information technology best practices - Roehl-Anderson, Janice M. (Hoboken, New Jersey : Wiley, 2013)
BAdd value to your organization via the mergers & acquisitions IT function/b/ As part of Deloitte Consulting, one of the largest mergers and acquisitions (M & A) consulting practice in the world, author Janice Roehl-Anderson reveals in iM & A Information Technology Best Practices/i how companies can effectively and efficiently address the IT aspects of mergers, acquisitions, and divestitures. Filled with best practices for implementing and maintaining systems, this book helps financial and technology executives in every field to add value to their mergers, acquisitions, and/or divestitures via the IT function./ ulliFeatures a companion website containing checklists and templates/liliIncludes chapters written by Deloitte Consulting senior personnel/liliOutlines best practices with pragmatic insights and proactive strategies/li/ul Many M & As fail to meet their expectations. Be prepared to succeed with the thorough and proven guidance found in iM & A Information Technology Best Practices/i. This one-stop resource allows participants in these deals to better understand the implications of what they need to do and how.
Preface -- Acknowledgments -- Introduction -- Introduction to the IT aspects of mergers, acquisitions, and divestitures / Varun Joshi, Saurav Sharma -- The role of IT in mergers and acquisitions / Peter Blatman, Eugene Lukac -- Aligning business and IT strategy during mergers, acquisitions and divestitures / Jason Asper, Wes Protsman -- Merger & acquisition it strategy, approach, and governance : IT and its customers / Chris DeBeer, Michael H. Moore -- Appendix A: M & A IT playbook overview / Joseph Joy, Shalva Nolen, Simon Singh, Nikhil Uppal -- Appendix B: Sample M & A IT checklists / Shalva Nolen, Sreekanth Gopinathan, Devi Aradada -- Appendix C: M & A IT sample case studies / Manish Laad, Abhishek Mathur Prasanna Rajanna -- About the editor -- About the companion website -- Index.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; Consolidation and merger of corporations; Business enterprises; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Business enterprises; Consolidation and merger of corporations; Information technology -- Management; Electronic books; Electronic books